Integrating father involvement into early childhood initiatives delivered at scale: key considerations - Nair, Sapna; Sinha, Harshula; Holding, Penny (Frontiers in Public Health, 2023)
Early child development (ECD) interventions, usually centered around the mother, exclude fathers from contributing to childcare. Research shows that a father’s involvement in childcare can have a positive impact on the child’s growth. In this light, a trial was conducted in rural India wherein a new program component aimed at enhancing fathers’ engagement in early child was incorporated into an existing childcare intervention. The paper highlights the learnings drawn from the trial to present pathways to change, that is, strategies needed to embed father involvement as a component within the intervention ecosystem.